Reforma do Ensino Médio: comunicação e construção de políticas públicas - disputas discursivas sobre educação das juventudes - Pezato, Priscila (2025)
This research analyzes the main discursive positions in the debate on education for youth in Brazil, focusing on the discussion of the reform of High School. The study observes the publication of the law named New High School. as emanating from a voice of power with questionable legitimacy (Butler, Bourdieu). It examines a government established following an impeachment process and a ritualistic approach to rushed approvals. We provide a brief historical overview of how the debate, processing, and changes to the New High School law unfolded, and we clarify the communicational contract underlying the market logic in which education is presented as a commodity that promises a place in the capitalist world, granting visibility to the individual within this system (McGowan, Laval). We explore, through discourse theory (Laclau and Mouffe), how the term “quality education” is treated in the debate as an empty signifier, allowing for various and contingent displacements and articulations, functioning as a unifying element for diverse and potentially antagonistic interests. We recognize the unmet demand for education, illustrated by student dropout rates and poor learning outcomes, and we follow the articulation of desires and claims through equivalential and antagonistic logic in the discourses of actors, constituting their collective identities from a position of lack (the gap), given the incapacity of language to represent the real. We aim to demonstrate attempts to patch the gap (stitching) and to fill the empty signifiers surrounding “quality education” across three discursive lines: (1) progressive neoliberals, politically aligned more towards the center, combining market productivity logic with socially recognition policies with a meritocratic bias, primarily represented in public-private partnerships and third-sector networks that established a heterarchical governance mode; (2) teachers and students, inheritors of Paulo Freire's thought, advocating for an emancipatory education that critiques the system and mitigates inequalities, organized in class movements; (3) ultraconservatives from the far right, tied to moral agendas, advocating for the militarization of schools and the denial of science and democratic institutions. We observe how political polarization has caused displacements in the articulatory chain, dividing society into two and reorganizing actors, demands, and identities in a new articulation in favor of a democratic project that has been called into question. Finally, we highlight the risks of a rational discourse of consensus and reiterate the essential role of passions and conflict in the dynamics of the political